2020
DOI: 10.3390/cells9041047
|View full text |Cite
|
Sign up to set email alerts
|

The P2X7 Receptor and NLRP3 Axis in Non-Alcoholic Fatty Liver Disease: A Brief Review

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease worldwide, and its prevalence is reaching epidemic characteristics both in adults and in children. The increase of NAFLD prevalence parallels that of obesity, now representing the major cause of liver inflammation, increasing the risk of cirrhosis and hepatocarcinoma. Furthermore, NAFLD is a risk factor for cardiovascular diseases and type 2 diabetes, two of the major leading causes of morbidity and mortality in western countries. Thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 59 publications
(102 reference statements)
0
18
0
Order By: Relevance
“…Studies suggest a significant role of NLRP3 inflammasome in the initiation and progression of metaflammation (i.e., metabolically-induced inflammation) and related diseases, such as obesity, T2DM, NAFLD, and atherosclerosis [15][16][17] . NAFLD is the most common liver disease and there are several studies suggesting that NLRP3 inflammasome, bridging inflammation and fibrosis, could play an important role and potentially representing novel targets for therapy in this disorder [18][19][20] . In support of this hypothesis, we have demonstrated that NLRP3 inflammasome is functional in the heart with the potential to regulate cardiac function and cell death 21 .…”
mentioning
confidence: 99%
“…Studies suggest a significant role of NLRP3 inflammasome in the initiation and progression of metaflammation (i.e., metabolically-induced inflammation) and related diseases, such as obesity, T2DM, NAFLD, and atherosclerosis [15][16][17] . NAFLD is the most common liver disease and there are several studies suggesting that NLRP3 inflammasome, bridging inflammation and fibrosis, could play an important role and potentially representing novel targets for therapy in this disorder [18][19][20] . In support of this hypothesis, we have demonstrated that NLRP3 inflammasome is functional in the heart with the potential to regulate cardiac function and cell death 21 .…”
mentioning
confidence: 99%
“…Damaged cells releasing ATP provoke activation of P2X7 and induce the NLRP3 inflammasome. As the authors highlight, these processes critically contribute to the induction of NAFLD and NASH [20].…”
Section: Mediators and Pathways In Hepatic Fibrosismentioning
confidence: 99%
“…Therefore, understanding of assembly, functionality and downstream signaling molecules of these multi-competent particles can open new opportunities in the treatment of inflammatory liver disease. In this context, regulatory aspects of the NLR family pyrin domain-containing 3 (NLRP3) inflammasome are discussed by Rossato and colleagues [20]. In their review article, the authors discuss that the activation of this inflammasome is driven by extracellular ATP resulting in the activation of a specific purinergic, ligand-gated ion channel termed P2X7.…”
Section: Mediators and Pathways In Hepatic Fibrosismentioning
confidence: 99%
“…In a broader perspective, emerging evidence shows the involvement of the P2X7R-NLRP3 inflammasome pathway in the induction of non-alcoholic fatty liver disease (NAFLD) and liver fibrosis, suggesting possible therapeutic strategies targeting the P2X7 receptor/NLRP3 inflammasome [ 99 ]. In a CCL4-induced, nonhuman primate model of liver fibrosis, treatment with a P2RX7 inhibitor (SGM-1019) improved histological characteristics of non-alcoholic steatohepatitis (NASH), protecting from liver inflammation and fibrosis [ 100 ].…”
Section: Conclusion and Therapeutic Perspectivesmentioning
confidence: 99%